2015
DOI: 10.3390/nu7064139
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vitamin D in Reproductive Health—A Trojan Horse or the Golden Fleece?

Abstract: In the last decade, vitamin D was in the spotlight in many fields of research. Despite numerous publications, its influence on reproductive health remains ambiguous. This paper presents an up-to-date review of current knowledge concerning the role of cholecalciferol in human reproduction. It covers various infertility issues, such as polycystic ovary syndrome, endometriosis, myoma-induced infertility, male infertility, premature ovary failure and in vitro fertilization techniques. Vitamin D deficiency, defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
1
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 66 publications
2
40
1
9
Order By: Relevance
“…Low vitamin D level has been linked to major common health problems in populations, particularly inflammatory conditions such as cardiovascular disease, cancers, diabetes, autoimmune diseases including multiple sclerosis, rheumatoid arthritis, and others [3]. In addition, vitamin D deficiency is a predisposing factor for various female diseases such as osteoporosis, uterine fibroids, endometriosis, and breast cancer and a risk factor for obstetrical complications such as gestational diabetes and preeclampsia [4,5]. Recently, we have reported that 47.4% of women with recurrent pregnancy losses (RPL) have vitamin D deficiency [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low vitamin D level has been linked to major common health problems in populations, particularly inflammatory conditions such as cardiovascular disease, cancers, diabetes, autoimmune diseases including multiple sclerosis, rheumatoid arthritis, and others [3]. In addition, vitamin D deficiency is a predisposing factor for various female diseases such as osteoporosis, uterine fibroids, endometriosis, and breast cancer and a risk factor for obstetrical complications such as gestational diabetes and preeclampsia [4,5]. Recently, we have reported that 47.4% of women with recurrent pregnancy losses (RPL) have vitamin D deficiency [6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, vitamin D deficiency is a predisposing factor for various female diseases such as osteoporosis, uterine fibroids, endometriosis, and breast cancer and a risk factor for obstetrical complications such as gestational diabetes and preeclampsia [4,5]. Recently, we have reported that 47.4% of women with recurrent pregnancy losses (RPL) have vitamin D deficiency [6].…”
mentioning
confidence: 99%
“…7,16,[17][18][19] [20][21][22] Genel olarak PCOS'ta vitamin D eksikliğinin obeziteyle birlikte insülin reseptör ekspresyonunu azaltarak ya da insülin üretimini/direncini artıra-rak glukoz transportunu bozup metabolizmasını değiştirdiği düşünülmektedir (Şekil 1). 7,11 Vitamin D, IR ile ilişkili insülin salımının dü-zenlenmesi, insülin reseptör ekspresyonunun uyarılması, insülin duyarlılığının değişimi ve inflamatuar sitokinlerin baskılanması gibi çeşitli doğru-dan ve dolaylı etkileriyle glukoz metabolizmasında görev almaktadır. 4,24 İnsülinsalımı üzerindeki doğru-dan etkisini pankreatik β-hücrelerinde eksprese olan VDR'nin aktivasyonu aracılığıyla göstermektedir.…”
Section: Vi̇tami̇n D Ve Poli̇ki̇sti̇k Over Sendromuunclassified
“…13 Obezite, vitamin D'nin adipoz dokuda birikmesi ve hirsutizm nedeniyle güneşlenmekten kaçınma gibi durumların etkisiyle PCOS'lu kadınların %67-85'sinde vitamin D eksikliği (<20 ng/ml) görül-mektedir. 7,11,13 Literatürde vitamin D eksikliğinin, obezite, IR, menstrüel disfonksiyon, kardiyovaskü-ler olumsuzluklar, infertilite gibi PCOS ile ilişkili durumlara katkısı olabileceğini ileri süren çok sayıda çalışma mevcuttur. 4,6,7,11,[20][21][22]30,36,[38][39][40][41] Ancak PCOS'lu kadınların vitamin D düzeylerinin değiş-mediği, düşük ya da yüksek bulunduğu çalışmalar da mevcuttur.…”
Section: Vi̇tami̇n D Ve Poli̇ki̇sti̇k Over Sendromuunclassified
“…(8) and also by others (9) did not show lower levels compared to controls. The literature in the field is ambiguous, showing both the importance of its adequate level and the lack of effect in infertility issues, such as polycystic ovary syndrome, endometriosis, myoma-induced infertility, male infertility, premature ovary failure and in vitro fertilization techniques (10,11). Interestingly, however, Lopes and cols.…”
mentioning
confidence: 99%